Essentials of game theory : a concise, multidisciplinary introduction - Leyton-Brown, Kevin 1975- (Synthesis lectures on artificial intelligence and machine learning, 2008)
Game theory is the mathematical study of interaction among independent, self-interested agents. Its imprint has become quite broad, and beside in economics, its traditional application area, is strongly felt today in disciplines as diverse as computer science, political science, biology, psychology, linguistics, sociology, and electrical engineering, among many others. This book provides a concise and accessible introduction to the field, covering the common basis that any member of this multidisciplinary audience is likely to require. It minimizes notation without sacrificing rigor, and ruthlessly focuses on essentials.